Securing SQL Server: Protecting Your Database from Attackers - Cherry, Denny (Elsevier Science & Technology Books, 2015)
Authored by Denny Cherry, a Microsoft SQL MVP and one of the biggest names in SQL server, this book will teach you how to properly secure an SQL server database from internal and external threats using best practices as well as specific tricks that he employs in his role as a consultant for some of the largest SQL server deployments in the world. --